2015
DOI: 10.1507/endocrj.ej15-0122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of one-hour postchallenge glucose on the relationship between insulin sensitivity and secretion

Abstract: The impact of postchallenge glucose on the relationship between insulin sensitivity (SI) and secretion (β) is unknown. We analyzed data from 2,264 health examinees (male/female 1,524/740, median age 54 yrs) with normal glucose tolerance (NGT, n = 1,623), non-diabetic hyperglycemia (NDH, n = 555), or diabetes (DM, n = 86) using OGTT-derived indices of SI (insulin sensitivity index [ISI]-Matsuda, 1/HOMA-IR, and 1/fasting IRI) and β (δIRI0-30/δPG0-30, and Stumvoll 1st [Stumvoll-1] and 2nd [Stumvoll-2] phases). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 33 publications
0
20
2
Order By: Relevance
“…The following indices were utilized in this study: Insulinogenic index = ΔIRI 0-30 / Δplasma glucose (PG) 0-30 [16]; homeostasis model assessment of insulin resistance (HOMA-IR) = [fasting plasma glucose (FPG) × fasting IRI (FIRI)] / 405 [17]; ISI matsuda = 10,000 / [sqrt (FPG × FIRI × mean PG × mean IRI)] [18], where mean PG and mean IRI represent mean glucose and insulin concentrations during the OGTT; and the disposition index = Stumvoll-1 / HOMA-IR, which was shown to have the best-fit hyperbolic line for insulin sensitivity and insulin secretion in Japanese [19]. Stumvoll-1 = 1,283 + 1.829 × IRI 30 -138.7 × PG 30 + 3.772 × FIRI [20].…”
Section: Measurements and Calculation Of Indicesmentioning
confidence: 99%
“…The following indices were utilized in this study: Insulinogenic index = ΔIRI 0-30 / Δplasma glucose (PG) 0-30 [16]; homeostasis model assessment of insulin resistance (HOMA-IR) = [fasting plasma glucose (FPG) × fasting IRI (FIRI)] / 405 [17]; ISI matsuda = 10,000 / [sqrt (FPG × FIRI × mean PG × mean IRI)] [18], where mean PG and mean IRI represent mean glucose and insulin concentrations during the OGTT; and the disposition index = Stumvoll-1 / HOMA-IR, which was shown to have the best-fit hyperbolic line for insulin sensitivity and insulin secretion in Japanese [19]. Stumvoll-1 = 1,283 + 1.829 × IRI 30 -138.7 × PG 30 + 3.772 × FIRI [20].…”
Section: Measurements and Calculation Of Indicesmentioning
confidence: 99%
“…It is obvious that one cannot a priori assume that individuals with a low FPG have robust beta cell function and vice versa. The idea of defining DI as HOMA-β%/HOMA-IR might have arisen from the authors' understanding that 'DI is assumed to be hyperbolic (the constant product of insulin sensitivity and insulin secretion) for individuals with the same degree of glucose tolerance,' which is not always correct [4,5]. A hyperbolic relationship between indices of insulin sensitivity (SI) and insulin secretion exists for a certain combination of the two, but not for all combinations [4,5].…”
Section: Disposition Index Firi Fasting Immunoreactive Insulin Fpgmentioning
confidence: 99%
“…The idea of defining DI as HOMA-β%/HOMA-IR might have arisen from the authors' understanding that 'DI is assumed to be hyperbolic (the constant product of insulin sensitivity and insulin secretion) for individuals with the same degree of glucose tolerance,' which is not always correct [4,5]. A hyperbolic relationship between indices of insulin sensitivity (SI) and insulin secretion exists for a certain combination of the two, but not for all combinations [4,5]. There is certainly ethnic diversity, as inferred by Simonson et al [6], such that the relationship between the two in the Japanese population is different from that in white people [5].…”
Section: Disposition Index Firi Fasting Immunoreactive Insulin Fpgmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that, in intravenous glucose tolerance tests and oral glucose tolerance tests (OGTTs), SI and β of individuals with NGT and those with glucose intolerance demonstrate hyperbolic relationships . Recently, the relationship between SI and β was analyzed for middle‐aged Japanese subjects predominantly with NGT . According to this study, 1/homoeostasis model assessment of insulin resistance (1/HOMA‐IR) and the Stumvoll first‐phase index (Stumvoll‐1) were selected as the best SI and β combination that produces a hyperbolic relationship.…”
Section: Introductionmentioning
confidence: 99%